Pengembangan Prototipe Aplikasi Berbasis Web untuk Pengenalan Batik Tradisional Indonesia - Mbuik, Genaldy Septianto; Pramartha, Cokorda Rai Adi (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Batik is one of the cultural arts recognized worldwide as a human heritage for oral and non-material culture by UNESCO since October 2009. It is known that in antiquity, the batik was a garment thatworn by relatives of the royal palace and not to be worn by commoners, even some patterns or motifs of batik can only be worn by certain groups because it has philosophical values and is used in traditional ceremonies. In Indonesia, batik has existed since the Majapahit era and was very popular in the following century. Until the 20th century all batik produced was written batik, which was only known as stamped batik. Therefore, batik is one of the cultural arts heritage that should be preserved and developed. The feature implemented in this application is a chatbot where the chatbot will provide messages containing information about batik motifs from each province in Indonesia. This application is also equipped with several features on the website, namely the home feature, the Indonesian batik feature, the historical feature that discusses the history of batik, and the chatbot feature.